2002
DOI: 10.1161/01.str.0000034396.68980.39
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Length of Stay of First-Ever Ischemic Stroke

Abstract: The severity of stroke, as rated by the total score on NIHSS, is an important factor that influences LOS after acute stroke hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
140
7
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 163 publications
(172 citation statements)
references
References 23 publications
21
140
7
4
Order By: Relevance
“…A related study revealed that smoking significantly decreased LOS by approximately 1.2 days. 1 We do not know the extent to which the change of significant association was attributed to sex or other suppresser variables or if it was primarily due to these study data.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…A related study revealed that smoking significantly decreased LOS by approximately 1.2 days. 1 We do not know the extent to which the change of significant association was attributed to sex or other suppresser variables or if it was primarily due to these study data.…”
Section: Discussionmentioning
confidence: 87%
“…1 Patients who received acute thrombolytic therapy were excluded. In this study costs were hospital charges because real costs were not available.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the classification of stroke types appears to be sufficiently accurate for use in epidemiological studies because CT and/or MRI are performed in almost all stroke patients. 27,28 Six air-quality monitoring stations were established in Kaohsiung by the Environmental Protection Administration. The monitoring stations are fully automated and provide readings of SO 2 , PM 10 , NO 2 , CO, and O 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Menurut pernyataan kebijakan American Heart Association, biaya penatalaksaan stroke akan meningkat dua kali lipat pada tahun 2030, dan insidensi kejadian stroke akan meningkat pada penduduk Amerika yang berusia 45-64 tahun. Peningkatan ini terjadi karena beberapa alasan diantaranya biaya untuk penatalaksanaan stroke di AS yang meningkat di tahun 2010 dari $71.55 miliar dollar menjadi $183.13 milyar dollar, biaya akibat hilangnya produktivitas meningkat $33.65 miliar dollar menjadi $56.54 miliar dollar setiap tahunnya, peningkatan prevalensi penduduk AS yang terkena stroke sebesar 5.1% 3 . Stroke juga menduduki angka kematian tertinggi di Indonesia menurut Riskesdas 2013.…”
unclassified